2013
DOI: 10.1590/s0100-40422013000800003
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of volatiles from male and female specimens of Baccharis trimera collected in two distant regions of southern brazil: a comparative study using chemometrics

Abstract: Recebido em 25/10/12; aceito em 5/5/13; publicado na web em 17/7/13 GC/MS/FID analyses of volatile compounds from cladodes and inflorescences from male and female specimens of Baccharis trimera (Less.) DC. collected in the states of Paraná and Santa Catarina, Brazil, showed that carquejyl acetate was the primary volatile component (38% to 73%), while carquejol and ledol were identified in lower concentrations. Data were subjected to hierarchical cluster analysis and principal component analysis, which confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
3
8
0
Order By: Relevance
“…For Baccharis trimera samples collected in different states of southern Brazil, the PCA analysis separated the samples into two distinct groups: volatile samples extracted from the cladodes and from shoots or inflorescences. Nevertheless, similarly to the results here presented, the authors suggested that the same chemotype of B. trimera occurs in the three southern states of Brazil and the strongest factor to discriminate the oils in that species seems to be the plant organ from where it is collected [49]. For the same species, environmental conditions have been shown to exert significant influence on essential oil biosynthesis [50].…”
Section: Essential Oil Chemical Compositionsupporting
confidence: 81%
“…For Baccharis trimera samples collected in different states of southern Brazil, the PCA analysis separated the samples into two distinct groups: volatile samples extracted from the cladodes and from shoots or inflorescences. Nevertheless, similarly to the results here presented, the authors suggested that the same chemotype of B. trimera occurs in the three southern states of Brazil and the strongest factor to discriminate the oils in that species seems to be the plant organ from where it is collected [49]. For the same species, environmental conditions have been shown to exert significant influence on essential oil biosynthesis [50].…”
Section: Essential Oil Chemical Compositionsupporting
confidence: 81%
“…Therefore the use of appropriate statistical techniques is usually required when quality control programmes are conducted in food companies. In this regard, chemometric tools, also known as multivariate statistical techniques, have been extensively applied in food science and technology, such as for assessing the authenticity of commercial UHT milk and evaluating the quality of Brazilian sugarcane spirits, herbal teas, red wines, dairy products, essential oils and soy‐based products, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in agreement with those reported by Besten et al [ 20 ], which showed clear similarities between the metabolism of male and female specimens of five different Baccharis species. In another study, Besten et al [ 32 ] verified that there was no significant difference in the chemical composition of B. trimera essential oils from Southern Brazil. However, our results suggest that the chemical composition of essential oils from Baccharis genus was clearly influenced by the species identified and the geographical region where the plant was collected.…”
Section: Resultsmentioning
confidence: 99%